The involvement of community pediatricians in the treatment of developmental-behavioral difficulties as perceived by directors of child development centers - Rachel Nissanholtz-Gannot; Davidovitch Michael; Yael Ashkenazi; Zachi Grossman (Israel Journal of Health Policy Research, 2021)
Abstract Background Developmental-behavioral issues are among the most frequent and disabling conditions of children and adolescents seen in ambulatory settings. Guidelines of the Israeli Pediatric Association and the Israeli Society for Developmental Pediatrics specify the role of the primary-care pediatrician in screening and early identification of mild developmental behavioral conditions and define the criteria for referral to child development institutes. The aims of this study were to examine and describe how directors of these institutes perceive the role and involvement of community pediatricians in child development. Methods Qualitative interviews of the directors of 22 child development institutes from the ministry of health and the four health plans. Results According to the interviewees, there is little involvement of community pediatricians in detecting developmental delays, and it is mainly nurses and preschool teachers who detect such delays. They report that the key barriers that deter community pediatricians from greater involvement in child development diagnosis and treatment are lack of time, lack of compensation, and insufficient clinical knowledge. The interviewees would like to see community pediatricians conducting the primary medical evaluation, providing parental guidance, referring to therapists in mild cases, exercising discretion before referring children to child development institutes and providing relevant information to the institutes in the referral process. The mechanisms that they proposed for increasing the involvement of community pediatricians were expansion of pediatricians’ training, increased pediatricians’ use of teleconsultation with child development specialists and incentives for thorough performance of developmental assessments. Conclusions Due to the importance of the Issue, we strongly recommend that policymakers require child development principles, evaluation, and providing appropriate parental guidance in the curriculum of the Israeli pediatric residency program. In addition, health plans should compensate pediatricians who need to conduct longer visits for children with developmental delays. The health plans should also develop teleconsultation channels for pediatricians with child development specialists to reduce unnecessary referrals to child development institutes.